Effect of risk factors of bronchial asthma on elderly health related quality of life at assiut university hospital, Egypt - Barakat, Nermeen Mahmoud Abd Elaziz (International Journal of Advanced Nursing Studies, 2016)
The present study aimed to assess quality of life of elderly asthmatics and to determine risk factors that may influence it. The study was carried out in the chest out-patient clinics and chest departments at Assiut University Hospital. The sample type of this study total coverage during one year consists of one hundred and five elderly people aged 60 years and above suffering from bronchial asthma disease. Two tools were used for data collection, tool one divided into three parts, socio-demographic data risk factors assessment, and history of bronchial asthma. Tool two to assessment health related quality of life of asthmatic patients was using St. George's Respiratory Questionnaire (SGRQ). The main results yielded by the study proved that, there were highly significant differences between risk factors of bronchial asthma disease and health-related quality of life. The study recommended that further research be implemented to improve the effect of health related quality of life for asthmatic patients.